2015
DOI: 10.1186/s12967-015-0727-2
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of malignant phenotypes of human glioblastoma cells by β-elemene through β-catenin-mediated regulation of stemness-, differentiation- and epithelial-to-mesenchymal transition-related molecules

Abstract: BackgroundGlioblastoma is the most common and lethal type of primary brain tumor. β-Elemene, a natural plant drug extracted from Curcuma wenyujin, has shown strong anti-tumor effects in various tumors with low toxicity. However, the effects of β-elemene on malignant phenotypes of human glioblastoma cells remain to be elucidated. Here we evaluated the effects of β-elemene on cell proliferation, survival, stemness, differentiation and the epithelial-to-mesenchymal transition (EMT) in vitro and in vivo, and inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Comparatively, β-elemene, as a traditional anti-cancer Chinese herbal medicine, has been approved by the state Food and Drug Administration of China for the treatment of malignant effusion and some solid tumors. It also exhibited a wide range of anticancer effects with low toxicity and few side-effects in vitro and in vivo (20,28). Numerous basic studies have concluded that β-elemene has strong antitumor activity on human GBM cell lines, as well as on rats and glioblastomabearing nude mice by inhibiting cell proliferation, inducing tumor cell apoptosis, and arresting cell cycle processes (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, β-elemene, as a traditional anti-cancer Chinese herbal medicine, has been approved by the state Food and Drug Administration of China for the treatment of malignant effusion and some solid tumors. It also exhibited a wide range of anticancer effects with low toxicity and few side-effects in vitro and in vivo (20,28). Numerous basic studies have concluded that β-elemene has strong antitumor activity on human GBM cell lines, as well as on rats and glioblastomabearing nude mice by inhibiting cell proliferation, inducing tumor cell apoptosis, and arresting cell cycle processes (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of elemene and gefitinib profoundly impairs epithelial cell transformation to mesenchymal cells, in a large part due to the regulation of the enhancer of zeste homolog 2 (EZH2), a carcinogenic histone methyltransferase and gene transcription regulator, thereby modulating the subsequent effector molecule required for cancer progression [153]. β-Catenin may also be the target of β-elemene in reversing the malignant phenotype of tumor cells; moreover, notch1, sonic hedgehog, and the epithelial marker of Ecadherin are upregulated by β-elemene in human glioblastoma cells in vitro and in vivo [19]. β-Elemene-mediated blockade of the phenotype transition of type 3 EMT in metastatic malignant tumors under the continuous stimulation of inflammation may also be an important antitumor mechanism of β-elemene.…”
Section: β-Elemenementioning
confidence: 99%
“…Currently, β-elemene and its derivatives have been utilized to treat various tumors including lung cancer [10], liver cancer [11], brain cancer [19], breast cancer [20], ovarian cancer [21], stomach cancer [16], prostate cancer, and other tissues for over 20 years [22]. Their practical and effective medicinal value has been confirmed gradually.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, β-elemene regulates several key molecules of tumor angiogenesis and metastasis, such as VEGF and matrix metalloproteinase, in addition to modulating the expression of ncRNAs that contribute to anticancer activities. [21][22][23][24][25][26][27][28][29][30][31][32][33][34] However, the clinical application of elemene has been limited by its poor solubility in water, poor stability, and low bioavailability. Therefore, studying a new drug delivery system for elemene has important significance.…”
Section: Introductionmentioning
confidence: 99%